1983
DOI: 10.1007/bf01308157
|View full text |Cite
|
Sign up to set email alerts
|

Drug and treatment efficacy of chenodeoxycholic acid in 97 patients with cholelithiasis and increased surgical risk

Abstract: Patients with symptomatic cholelithiasis who represent higher than normal surgical risks may be the most suitable candidates for medical dissolution of gallstones. Chenodeoxycholic acid was given to 97 patients in a dosage of 15 mg/kg of body weight per day for a period of two years. Complete gallstone dissolution occurred in 27 of 97 patients (28%). If dropouts are excluded then the success rate is 27 of 64 patients (42%). Diarrhea was a common but manageable side effect for most. Thirty-two percent of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The presence of calcium salts in the gallstones, observed as calcification in CT images, reduces the efficacy of UCDA therapy [14][15][16][17]. However, clinical studies show that if good candidates for medical treatment are selected, up to 60% are completely cleared of CBD stones after 12-24 months of treatment [7,8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of calcium salts in the gallstones, observed as calcification in CT images, reduces the efficacy of UCDA therapy [14][15][16][17]. However, clinical studies show that if good candidates for medical treatment are selected, up to 60% are completely cleared of CBD stones after 12-24 months of treatment [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Although the treatment of choice for cholelithiasis is cholecystectomy, patients with small cholesterol stones, without severe symptoms, and proper function of the gallbladder receive UDCA therapy, if they are not good candidates for surgery. Studies indicate that up to 60% of patients have a chance to completely recover from CBD stones with pharmacotherapies if they are good candidates for medical treatment [7,8].…”
mentioning
confidence: 99%
“…Oral administration of the bile acids CDCA [128][129][130][131][132][133][134][135][136][137][138][139][140][141] and UDCA [142-1551 alone or in combination [146,156,157] is associated with decreased cholesterol SI of gallbladder bile and with cholesterol gallstone dissolution in man. It was originally suggested that bile acids might lower cholesterol SI by expanding [I 581 the reduced bile acid pool size in cholesterol gallstone disease [I 171, thus restoring bile acid secretion to normal.…”
Section: Effect Of Bile Acid Therapymentioning
confidence: 99%
“…12 3/9 47(8) 114(4) (2) UDCA (MT) 12 2/10 55 (6) 107 (5) 11-8 (3) UDCA (BT) 12 4/8 55 (9) 102 (6) 12-3 (3) Combination (BT) 10 2/8 50 (6) 118 (5) 13-2 (2) MT= mealtime; BT= bedtime; IBW= ideal body weight * Results expressed as mean (SEM) 0 0 28 0 0 30 25 38 18 20 30 19 23 52 28 10 10 30 27 27 18 48 80 18 8 8 20 25 40 26 43 65 13 45 50 12 50 100 13 100 100 14 68 90 12 65 78 11 100 100 13 75 93 10 60 80 11 27 52 11 0 0 10 73 73 9 90 95 7 47 80 7 100 100 7 85 85 6 80 92 5 0 0 5 40 56 6 26 76 7 70 90 5 50 70 5 90 100 4 80 100 4 100 100 4 50 100 4 100 100 4 100 100 4 100 100 4 36 56 4 60 78 3 85 85 4 DIA=initial gallstone diameter; DR6 and DR12=dissolution rate at 6 and 12 months respectively; *= DR in this matched quartet of patients is calculated from % reduction in pretreatment gall stone numbers.…”
mentioning
confidence: 99%